Towards a comprehensive picture of the star cluster age–metallicity relationship in the Small Magellanic Cloud - Piatti, Andres Eduardo (2011)
We present the results on the age and metallicity estimates of 11 Small Magellanic Cloud (SMC) clusters obtained from CCD Washington CT1T2 photometry. The 11 clusters reproduce the ∼2 Gyr bursting formation paradigm when entering them into the age–metallicity relationship (AMR). Once these clusters were added to the largest known SMC cluster sample with ages and metallicities put into an homogeneous scale, we found that a comprehensive picture of the cluster AMR can be obtained, which includes the following components: two enhanced formation processes at t ∼ 2 and 5–6 Gyr, which have taken place throughout the entire body of the galaxy; the absent of a metallicity gradient and a relative spread in metallicity for clusters older than ∼7 Gyr. Furthermore, such picture should not significantly change due to incompleteness in the number of studied clusters. Indeed, based on the statistics of catalogued and studied clusters, we found that a total of seven relatively old/old clusters have not yet studied, and even a smaller number is obtained if the cluster spatial distribution is considered.